Preliminary results of the geological structure and kinematics of deformation in Mt. Tzena (Paikon subzone, Central Macedonia, Greece) - ΚΑΤΡΙΒΑΝΟΣ Ε.; ΜΟΥΝΤΡΑΚΗΣ Δ.; ΚΙΛΙΑΣ Α.; ΠΑΥΛΙΔΗΣ Σ. (Bulletin of the Geological Society of Greece, 2001)
The Tzena Mt. belongs to the Paikon subzone (Axios zone, Central Macedonia, Greece) and consists of 5 distinguishable lithological units, which are from the lower to the upper the following: the lower unit of gneisses, the marbles unit, the black phyllites, the meta-volcanosedimentary unit and the meta-flysch. These units form a metamorphic sedimentary sequence of Upper Paleozoic to Lower Cretaceous age, while the metarhyolites of the volcanosedimentary unit are of Jurassic age. Kinematic analysis of the deformation in Tzena Mt. suggests that the whole metamorphic sequence has been affected by a strong shearing and mylonitisation in ductile to semi-ductile conditions, trending SW-NE, contemporaneous with a retrograde metamorphism in greenschist facies. Kinematic indicators show sense of movement both top to the SW and NE while a streching lineation, trending SW-NE, defined by preferred orientation of white mica and chlorite remains stable all over the metamorphic sequence. The Upper Cretaceous carbonates of the adjacent to Tzena, Pinovon Mt., have been affected by this deformation as well, and hence the deformation took place in Tertiary times. However, the contact between the lower gneiss unit and the marbles unit constitute a shear zone, in ductile to semi-ductile conditions, trending SW-NE with a sense of shear top to the SW. Thus, the marbles have been moved upon the gneisses along a large shear zone towards SW, during the Tertiary deformation. Correlation between this tertiary SW-NE deformation event in Tzena Mt. with the similar tertiary shear deformation towards SW in Paikon Mt., suggests that Tzena and Paikon Mts. have the same tectonic history in Tertiary times. Analogous Tertiary tectonic events with similar geometry and kinematics of the deformation have already been established for several other areas in Greece (Olympos - Ossa Mts., Rhodope Mt., Cyclades islands etc.) where they have caused the exhumation of metamorphic core complex (Kilias & Mountrakis, 1990, Sokoutis et al., 1993, Kilias, 1995, Dinter, 1998, Kilias et al., 1999). Thus, in relation to these, an exhumation of the Tzena orogen, consisting of the metamorphic sequence, during the Tertiary extensional tectonic process could be very possible.